Hubungan Ranah Sumber dan Ranah Target dalam Ungkapan Metaforis Tentang Pendidian di Media Sosial X - Ida Bagus Made Ari segara (SPHOTA: Jurnal Linguistik dan Sastra, 2024)
This study aims to identify conceptual metaphors about education on the social media platform X, as well as the types of metaphors that emerge from observing the phenomenon of educational development in Indonesia, which prompts people to express their emotions on Twitter. Because the use of conceptual metaphors likely occurs unintentionally, resulting in diverse forms, this study seeks to explore the relationship between the source domain and the target domain in metaphorical expressions unintentionally produced by individuals about education. The data in this study is qualitative; data collection was done by documenting and observing data on the social media platform X, aided by note-taking techniques to record the data found, which was then analyzed using the conceptual metaphor theory of Kovecses (2006), which divides metaphors into three types: structural, orientational, and ontological. The study's results show the forms of conceptual metaphors found include education as a place, education as wealth, good as up, bad as down, and education as an entity.